Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Dan Corporate Social Responsibility Terhadap Penghindaran Pajak - Zara Fadhilla Firdaus; Endah Sri Wahyuni (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
The purpose of this study is to analyze the influence of profitability, leverage, firm size, and corporate social responsibility on tax avoidance. This research employs a quantitative approach using secondary data sources. A purposive sampling technique was applied, resulting in a sample of 37 companies that met the criteria from a total of 83 observations. The research objects are mining sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The data analysis technique used is multiple regression analysis, accompanied by classical assumption tests, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation, as well as hypothesis testing. The results of this study show that profitability has a negative effect on tax avoidance. Leverage and firm size have no significant effect on tax avoidance, while corporate social responsibility has a positive effect on tax avoidance. This study is expected to raise awareness among entities to refrain from engaging in tax avoidance practices and to fulfill their tax obligations in accordance with applicable regulations.